Space of Library in Post-Method Pedagogy - Guragain, Keshav (Access: An International Journal of Nepal Library Association, 2024)
A library is a source of knowledge in which varied learning resources are found under a single roof. It is also a space for new experiments and innovations. On the other hand, Post method pedagogy is an emerging issue in teaching and learning. For now, new teaching approaches, methods, and techniques have come into existence. The reason behind it is to fill the gaps left by the previous methods. In other words, existing methods could not be able to represent the ways of teaching the learning process at that time. Gradually, new methods came into existence. Post method pedagogy has come up with a solution for the 21st century. This article has tried to dig out the point where the DNA of post-method pedagogy and the purpose of library use are found in the point of teaching and learning. Furthermore, this article expects to flag the concept of linking up the library and library materials with post-method pedagogy.